Climate change and sustainable development : Ethical perspectives on land use and food production - Meisch, Simon; Potthast, Thomas (Wageningen Academic Publishers, 2012)
Climate change is a major framing condition for sustainable development of agriculture and food. Global food production is a major contributor to global greenhouse gas emissions and at the same time it is among the sectors worst affected by climate change. This book brings together a multidisciplinary group of authors exploring the ethical dimensions of climate change and food. Conceptual clarifications provide a necessary basis for putting sustainable development into practice. Adaptation and mitigation demand altering both agricultural and consumption practices. Intensive vs. extensive production is reassessed with regard to animal welfare, efficiency and environmental implications. Property rights pay an ever-increasing role, as do shifting land-use practices, agro-energy, biotechnology, food policy to green consumerism. And, last but not least, tools are suggested for teaching agricultural and food ethics. Notwithstanding the plurality of ethical analyses and their outcome, it becomes apparent that governance of agri-food is faced by new needs and new approaches of bringing in the value dimension much more explicitly. This book is intended to serve as a stimulating collection that will contribute to debate and reflection on the sustainable future of agriculture and food production in the face of global change.